Sistem Parkir Berbasis RFID dan Pengenalan Citra Pelat Nomor Kendaraan - Eko Didik Widianto; Herrizal Muhammad Wijaya; Ike Pertiwi Windasari (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2017)
The length of time in manually recording vehicle license plates in the parking system leads to long vehicle queues. This research developed automatic parking system based on RFID and vehicle plate number recognition. Authentication used a camera and Arduino Uno as the controller for RFID reading, feedback and gatekeeper control. The system will compare the character's image and RFID in the record of the database to authorize a vehicle. Image processing was done by contour analysis method and had 91% in accuracy at 60 cm of distance and 131.89 milliseconds of reading speed. The system had been able to work to automatically open and close gates based on the match of RFID and vehicle plate number recognition.